High blood pressure in dementia: How low can we go? - Yuda Turana (2020)
© 2019 Wiley Periodicals, Inc. Hypertension is an important public health concern. The prevalence keeps increasing, and it is a risk factor for several adverse health outcomes including a decline in cognitive function. Recent data also show that the prevalence of hypertension and age-related dementia is rising in Asian countries, including in the oldest old group. This study aims to discuss possible treatments for high blood pressure in the elderly and propose an optimal target for BP relative to cognitive outcomes. This review discusses several studies on related blood pressure treatments that remain controversial and the consequences if the treatment target is too low or aggressive. Longitudinal, cross-sectional, and RCT studies were included in this review. An optimum systolic blood pressure of 120-130 mm Hg is recommended, especially in nondiabetic hypertensive patients with significant risk factors. In the oldest old group of patients, hypertension might have a protective effect. The use of calcium channel blockers (CCB) and angiotensin receptor blocker (ARB) is independently associated with a decreased risk of dementia in older people. However, personalized care for patients with hypertension, especially for patients who are frail or very old, is encouraged.